Übermensch sebagai Radikalisasi Filsuf Alamiah (Krisis Pelampauan Diri Dalam Dunia Pendidikan Desain) - Ferdinand Indrajaya (Humaniora, 2013)
This writing is not an inquiry to classical philosophy per se but is an attempt to propose a dialogue. The content of this writing is a dialogue between classic realm of philosophical thought which is represented by Plato and the realm of thought from the end of modernity, which is represented by Friedrich Nietzsche. The proposed dialogue presented through this writing is not for the sake of permeating or exposing the dialogue, also, per se but is contextualized with the recent contemporary condition of academic world in general and design education in university in specific. What this writing tries to show and reflect is, first, a found similarity in Plato’s concept of education on natural born philosopher with Nietzsche’s übermensch. Secondly, there’s a sense of urgency for the features of übermensch within nowadays nihilistic society to arise. Manifested Übermensch is to embrace nihilism within prevailing stubborn condition of comodifying design higher education through formal templatization of creativity. This concern is relevant to Plato’s concept of education: it is not a matter of privatization through commodification, but since it is now, this might prepare a way for übermensch to emerge. Structurally, this writing is divided into three parts. The introduction reflects on contemporary condition of higher education (on design). Second, this article shares writer’s reflection of the similarities between Plato’s concept and Nietzsche’s on education. Lastly, it is to show the potentiality of Platonic approach on education to give birth to übermensch.